An Evaluation of the Prescription of Opioids for Chronic Nonmalignant Pain by Australian General Practitioners. Issue 1 (28th December 2012) - Holliday, Simon; Magin, Parker; Dunbabin, Janet; Oldmeadow, Christopher; Henry, Julie‐Marie; Lintzeris, Nicholas; Attia, John; Goode, Susan; Dunlop, Adrian
Abstract Objective. Our objective was to evaluate the quality of opioid analgesia prescribing in chronic nonmalignant pain (CNMP) by general practitioners (GPs, family physicians). Design. An anonymous, cross‐sectional questionnaire‐based survey. Setting. The setting was five Australian divisions of general practice (geographically based associations of GPs). Methods. A questionnaire was mailed to all division members. Outcome measures were adherence to individual recommendations of locally derived CNMP practice guidelines. Results. We received 404 responses (response rate 23.3%). In the previous fortnight, GPs prescribed long‐term continuous opioids for CNMP for a median of 4 and a mean of 7.1 (±8.7) patients with CNMP. Guideline concordance (GLC) was poor, with no GP always compliant with all guideline items, and only 31% GPs usually employing most items. GLC was highest for the avoidance of high dosages or fast‐acting formulations. It was lowest for strategies minimizing individual and public health harms, such as the initiation of opioids on a time‐limited trial basis, use of contracts, and the preclusion or management of aberrant behaviors. GLC was positively associated with relevant training or qualifications, registration with the Australian Prescription Drug Monitoring Programme, being an opioid substitution therapy prescriber, and female gender. Conclusions. In this study, long‐term opioids were frequently initiated for CNMP without a quality use‐of‐medicine approach. Potential sequelae are inadequate treatment of pain and escalating opioid‐related harms. These data suggest a need for improved resourcing and training in opioid management across pain and addictions.